Evaluation of efficacy of oral Tramadol as premedication in preventing post operative shivering after General Anesthesia - A Prospective Study (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Postoperative shivering (POS) is one of the most common complications after surgery. There are two methods to reduce the shivering, including pharmacological and non-pharmacological methods.Aim of the study: The present study is designed to compare the efficacy of 50 mg oral tramadol as premedication with placebo on prevention of POS after general anesthesia.Material and methods: This prospective study consisted of 80 adult patients scheduled for ENT surgery under general anesthesia. The patients were randomized into two groups of 40 patients each. Group I (tramadol group) received 50 mg of oral tramadol and group II (placebo) received an oral placebo 90 minutes before operation. All patients were assessed for postoperative shivering in the recovery room.Results: Regarding the efficacy of 50 mg oral tramadol as premedication in preventing POS the study revealed that incidence of POS was 10% in group I (Tramadol group), 45% in group II (Placebo group) and there was statistically significant difference between the groups according to incidence and severity of shivering.Conclusion: Oral tramadol premedication adequately prevents postoperative shivering after general anesthesia.J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 06-09